A postgraduate training programme in child and adolescent mental health in a lower-middle-income country: a partnership model from Nigeria - Olayinka Omigbodun; Cornelius Ani (BJPsych International, 2024)
This paper describes a postgraduate training programme in child and adolescent mental health (CAMH) in Nigeria. It explains the background, curriculum development, teaching, evaluation and outcomes. By its 10th year the programme had trained 166 CAMH professionals from 14 African countries. Many of the graduates are running clinical CAMH services in their countries, mostly pioneered by them. They are also conducting CAMH training, including as faculty on the programme, and some are in international CAMH leadership roles. Key success elements of the programme that can be replicated in other low- and middle-income countries include international partnership, adopting a train-the-trainer approach, using a curriculum that covers clinical aspects of CAMH while also developing leadership and research skills, use of free-access training resources, and access to seed funding.